Control Of Inventory Of Raw Materials For Wine Products By Form 2 Phase Inventory Using Material Requirement Planning (Case Study At Pt. Xyz) - Syifa Robbani; Ririn Fatman Nanda; Roisatun Nisa (JOFE : Journal of Food Engineering, 2023)
This research aims to analyzing the MRP method to obtain the lowest inventory costs of product wine. The raw material planning system carried out by PT XYZ uses sales data from the PPIC division to order all raw materials at one time. Preparing MRP requires input in the form of an ind schedule through the netting, lotting (economic order quantity (EOQ), lot for lot (LFL)), and offsetting. The output of the MRP method is a plan for ordering raw material requirements based on lead time. This MRP method can provide improvements to PT XYZ through the formation of a master production schedule, ordering schedule, and reducing inventory costs. Comparing the company's inventory costs with the MRP method for wine raw materials produces savings of 15% per year, and EOQ is more economical. SiO2 raw material produces savings of 55% per year, and EOQ is more economical. Purifying enzyme raw materials produces savings of 41% per year, and EOQ is more economical. The MRP process is carried out at 28% annually, and EOQ is more economical. Fermented extract raw materials produce savings of 14% per year, and LFL is more economical